Identification of Signatures of Selection by Whole-Genome Resequencing of a Chinese Native Pig - Zhang, Wei; Yang, Min; Zhou, Mei; Wang, Yuanlang; Wu, Xudong; Zhang, Xiaodong; Ding, Yueyun; Zhao, Guiying; Yin, Zongjun; Wang, Chonglong (Frontiers in Genetics, 2020)
Identification of genomic signatures of selection that help reveal genetic mechanisms underlying traits in domesticated pigs is of importance. Anqing six-end-white pig (ASP), a representative of the native breeds in China, has many distinguishing phenotypic characteristics. To identify the genomic signatures of selection of the ASP, whole-genome sequencing of 20 ASPs produced 469.01 Gb of sequence data and more than 26 million single-nucleotide polymorphisms. Combining these data with the available whole genomes of 13 Chinese wild boars, 157 selected regions harboring 48 protein-coding genes were identified by applying the polymorphism levels (θπ) and genetic differentiation (FST) based cross approaches. The genes found to be positively selected in ASP are involved in crucial biological processes such as coat color (MC1R), salivary secretion (STATH), reproduction (SPIRE2, OSBP2, LIMK2, FANCA, and CABS1), olfactory transduction (OR5K4), and growth (NPY1R, NPY5R, and SELENOM). Our research increased the knowledge of ASP phenotype-related genes and help to improve our understanding of the underlying biological mechanisms and provide valuable genetic resources that enable effective use of pigs in agricultural production.